Pendampingan Talenta Digital Kreatif dengan Keterampilan Video Content Creator Kota Palembang - Riesta Ayu Oktarina; Jokhanan Kristiyono; Ratna Puspita Sari; Suprihatin (Prapanca : Jurnal Abdimas, 2023)
The millennial generation is very synonymous with social media activities, not even a few are interested in becoming a content creator. Digital tourism is an integration between the development of Information and Communication Technology with the tourism industry. In line with this, one of the themes raised in the 2022 Digital Talent Scholarship (DTS) Program is video content creator training which aims to form the skills of the young workforce in the field of video production for various communication and marketing purposes through the wrong digital media. one of them supports the development of the tourism sector in Indonesia. The training is carried out offline, using a project-based learning method. In this method, participants gain knowledge, think critically, analyze, evaluate, and make decisions. it can be concluded, that the DTS TA (Thematic Academy) Video Content Creator Batch 2 activity in Palembang City is going according to plan. Participants are quite enthusiastic and can follow the lesson easily. Various creativity and ideas emerged from the participants who were shown in the tasks they made.